Integrative conductance of oxygene during exercise at altitude (International hypoxia symposia 2009. Hypoxia and exercise. 10-14 March 2009, 2009)
In the oxygen (02) cascade downstream steps can never achieve higher flows of Ü2 than the preceding ones. At the lung the transfer of O2 is determined by the Ü2 gradient between the alveolar space and the lung capillaries and the Ü2 diffusing capacity (DL02). While DLÜ2 may be increased several times during exercise by recruiting more lung capillaries and by increasing the oxygen carrying capacity of blood due to higher peripheral extraction of O2, the capacity to enhance the alveolocapillary PC>2 gradient is more limited. The transfer of oxygen from the alveolar space to the hemoglobin (Hb) has to overcome first the resistance offered by the alveolocapillary membrane (l/DM) and the capillary blood (1/OVc). The fractional contribution of each of these two components to DL02 remains unknown. During exercise these resistances are reduced by the recruitment of lung capillaries. The factors that reduce the slope of the oxygen dissociation curve of the Hb (ODC) (i.e., lactic acidosis and hyperthermia) increase l/0Vc contributing to limit DLÜ2. These effects are accentuated in hypoxia. Reducing the size the active muscle mass improves pulmonary gas exchange during exercise and reduces the rightward shift of the ODC. The flow of oxygen from the muscle capillaries to the mitochondria is supposedly limited by muscle O2 conductance (Dmc02J (an estimation of muscle oxygen diffusing capacity). However, during maximal whole body exercise in normoxia higher flow of O2 is achieved at the same pressure gradients after increasing blood [Hb], implying that in healthy humans exercising in normoxia there is a functional reserve in DmcO2. This conclusion is supported by the fact that during small muscle exercise in chronic hypoxia, peak exercise DmcO2 is similar to that observed during exercise in normoxia despite a markedly lower Ü2 pressure gradient driving diffusion.